Generate a Meta-Model Content for Collaboration Space of Learning Management System Compatible with IMS-LD - Ouadoud, Mohammed; Chafiq, Tarik; Rida, Nouha; Chkouri, Mohamed Yassin (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The context of this work is that of designing a Instructional Management Systems - Learning Design (IMS-LD) model for collaboration space of a Learning Management System (LMS). Our work is specifically in the field or seeking to promote, by means of information technology from a distance. Our approach is to first think about the conditions for creating a real collaboration space between learners, and designing the IT environment that supports this space. In this paper, we try to adapt the IMS-LD model with a collaboration model for Learning Management System based on the social constructivism. This adaptation will go through three stages. Firstly, the development of an LMS model. Secondly, the study of correspondence between the developed model and IMS-LD model. Finally their transformation to IMS-LD model.